2010
DOI: 10.1097/rli.0b013e3181ee5a9e
|View full text |Cite
|
Sign up to set email alerts
|

High Relaxivity Magnetic Resonance Imaging Contrast Agents Part 1

Abstract: Rationale and objectives The donor atoms that bind to gadolinium in contrast agents influence inner-sphere water exchange and electronic relaxation, both of which determine observed relaxivity. These molecular parameters impact relaxivity greatest when the contrast agent is protein bound. We sought to determine an optimal donor atom set to yield high relaxivity compounds. Methods Thirty-eight Gd-DOTA derivatives were prepared and relaxivity determined in presence and absence of human serum albumin as a funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 61 publications
0
97
0
Order By: Relevance
“…In 4.5 % w/v HSA, 60 MHz 37 °C, the relaxivity of the q=0 DOTA-picolinate derivative reported by Dumas et al 3 was 5.96 mM -1 s -1 , while the q=0 TTHA analog of MS-325 21 gave a relaxivity of 6.53 mM -1 s -1 . The fact that the relaxivities of [Gd( 6a )(H 2 O) 2 ] and [Gd( 6b )(H 2 O) 2 ] are higher suggests that while they certainly have decreased inner-sphere hydration, the inner-sphere water molecules are not entirely displaced.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…In 4.5 % w/v HSA, 60 MHz 37 °C, the relaxivity of the q=0 DOTA-picolinate derivative reported by Dumas et al 3 was 5.96 mM -1 s -1 , while the q=0 TTHA analog of MS-325 21 gave a relaxivity of 6.53 mM -1 s -1 . The fact that the relaxivities of [Gd( 6a )(H 2 O) 2 ] and [Gd( 6b )(H 2 O) 2 ] are higher suggests that while they certainly have decreased inner-sphere hydration, the inner-sphere water molecules are not entirely displaced.…”
Section: Resultsmentioning
confidence: 86%
“…Water exchange kinetics can be exquisitely tuned by changing the donor groups on the co-ligand or by steric crowding. 3-6 Rotational dynamics can be modulated by changing the molecular size, either by covalent 7, 8 9, 10 or noncovalent modification. 11-14 Control of internal motion is also paramount to optimizing relaxivity and elegant strategies have been elaborated to this end.…”
Section: Introductionmentioning
confidence: 99%
“…At a theoretical level these processes are understood, but in practice there are a number of molecular parameters involved which can make data interpretation challenging. We have employed an arsenal of magnetic resonance and optical techniques to interrogate hydration number, 76-79 metal-hydrogen distance, 80-82 rotational motion, 83-87 electronic relaxation, 88-90 water exchange kinetics, 85,91-95 and how these are impacted by protein binding. 78,85,87 …”
Section: Strategies For Increasing Relaxivitymentioning
confidence: 99%
“…90 We systematically explored this effect and found that pendant H-bond acceptors gave increased relaxivity provided there was one methylene unit between the amide N and the acid group. Thus amide pendants derived from glycine, iminodiacetic acid, aspartic acid, or aminomethylphosphonic acid gave a pronounced second sphere effect (Figure 6, complex type A).…”
Section: Hydrationmentioning
confidence: 99%
“…Unfortunately, clinical gadolinium-based contrast agents have water-exchange rates in the range of 10 6 –10 7 s −1 [23], far too slow to optimize the relaxivity of macromolecular complexes [24, 25, 26]. Since those early reports, complexes with fast water-exchange kinetics have been reported that do not limit the relaxivity of macromolecular derivatives [27, 28, 29]. These new complexes include the hydroxypyridone family of complexes [30], phosphonic acid derivatives of DOTA [31], and the extended DTPA analog EPTPA [32].…”
mentioning
confidence: 99%